Elevated Levels of Factor VII Activity in the Postprandial State: Effect of the Factor VII Arg-GIn Polymorphism - Silveira, Angela; Green, Fiona; Karpe, Fredrik; Blombäck, Margareta; Humphries, Steve; Hamsten, Anders (Thrombosis and Haemostasis, 1994)
A genetic polymorphism (Arg/Gln353) of coagulation factor VII was recently identified and shown to be associated with differences in basal factor VII coagulant activity. Postprandial lipaemia seems to exert an acute but evanescent effect on the activity of factor VII, and the influence of the Arg/Gln353 polymorphism on factor VII activation during postprandial lipaemia was therefore studied in male post-infarction patients [age 48.8 ± 3.3 years (mean ± SD)] with Arg/Arg (n = 23) and Arg/Gln (n = 8) genotypes. Factor VII antigen (VIlag) and activity along with plasma lipoproteins were determined before and after intake of a mixed meal-type of oral fat load. Patients with the Arg/Gln genotype had basal VIlag and activated factor VII (Vila) levels 75% and 48%, respectively, of those of patients homozygous for the Arg allele. In absolute terms, Vila increased more in homozygotes for the Arg allele (AO-6 h Vila 1.76 ± 1.48 ng/ml) than in heterozygotes (0.60 ± 0.27 ng/ml) in response to fat intake, but the percentage increase in Vila molecules did not differ significantly between subjects with Arg/Arg and Arg/Gln genotypes (37 ± 32% versus 27 ± 15%). This suggests that the influence of the Arg/Gln polymorphism on factor VII activity is mainly accounted for by differences in the basal factor VII protein level between genotypes. Since most of our lives are spent in the postprandial state, possession of the factor VII-Gln353 allele is likely to confer protection against coronary heart disease by reducing the amount of Vila produced in response to fat intake.